Measurement of electroweak production of a W boson and two forward jets in proton-proton collisions at root s=8 TeV - (:unkn) unknown (SPRINGER, 2016)
A measurement is presented of the cross section for the electroweak production of a W boson in association with two jets in proton-proton collisions at a center-of-mass energy of 8 TeV. The data set was collected with the CMS detector and corresponds to an integrated luminosity of 19.3 fb(- 1). The measured fiducial cross section for W bosons decaying to electrons or muons and for p(T)(j 1) > 60 GeV, p(T) (j 2) > 50 GeV, broken vertical bar eta(j)broken vertical bar < 4.7, and m (j j) > 1000 GeV is 0.42 +/- 0.04 (stat) +/- 0: 09 (syst) +/- 0: 01 (lumi) pb. This result is consistent with the standard model leading-order prediction of 0.50 +/- 0.02 (scale) +/- 0.02 (PDF) pb obtained with MADGRAPH5_aMC@NLO 2.1 interfaced to PYTHIA 6.4. This is the first cross section measurement for this process.
Keywords: Electroweak interaction; Hadron-Hadron scattering (experiments); PLUS PLUS; CERN LHC